Early Improvement and Marriage Are Determinants of the 12-Month Treatment Outcome of Paroxetine in Outpatients with Panic Disorder - Watanabe, Takashi (Clin Psychopharmacol Neurosci, 2017)
OBJECTIVE: In this study, we investigated the determinants of remission and discontinuation of paroxetine pharmacotherapy in outpatients with panic disorder (PD). METHODS: Subjects were 79 outpatients diagnosed with PD who took 10–40 mg/day of paroxetine for 12 months. The candidate therapeutic determinants included the serotonin transporter gene-linked polymorphic region and the −1019C/G promoter polymorphism of the serotonin receptor 1A as genetic factors, educational background and marital status as environmental factors, and early improvement (EI) at 2 weeks as a clinical factor were assessed. The Clinical Global Impression scale was used to assess the therapeutic effects of the pharmacotherapy. RESULTS: Cox proportional hazards regression was performed to investigate the significant predictive factors of remission and discontinuation. EI was only a significant predictive factor of remission. EI was a significant predictive factor of remission (hazard ratio [HR], 2.709; 95% confidence interval [CI], 1.177–6.235). Otherwise, EI and marital status were significant predictive factors of the discontinuation. EI (HR, 0.266; 95% CI, 0.115–0.617) and being married (HR, 0.437; 95% CI, 0.204–0.939) were considered to reduce the risk of treatment discontinuation. In married subjects, EI was a significant predictive factor of the discontinuation (HR, 0.160; 95% CI, 0.045–0.565). However, in unmarried subjects, EI was not a significantly predictive factor for the discontinuation. CONCLUSION: EI achievement appears to be a determinant of PD remission in paroxetine treatment. In married PD patients, EI achievement also appears to reduce a risk of discontinuation of paroxetine treatment.